Isolated Hepatobiliary Involvement in an Infant with Langerhans Cell Histiocytosis: A Case Report with Review of Literature - Niva Lakra; Abhik Paul; Ranajoy Ghosh; Supratim Datta (Wolters Kluwer Medknow Publications, 2023)
Background: Langerhans cell histiocytosis (LCH) is a rare condition in which there is the proliferation of cells of the monocyte-dendritic cell lineage, including Langerhan's cells, with variable clinical manifestations and outcomes. Hepatic involvement is often seen as a part of multi-system LCH and is associated with a fulminant course. Isolated hepatobiliary involvement in LCH is rare. Clinical Description: We report an 11-month-old female infant presenting with prolonged fever associated with progressive jaundice, clay-colored stools, and a massive hepatomegaly. Liver biopsy showed CD1a and Langerin positivity. There was no other system involvement, and hence, the infant was diagnosed with a case of single-system LCH with isolated hepato-biliary LCH. Management and Outcome: A customized chemotherapeutic regimen was started with cytarabine and prednisolone. The patient has responded and there has been gradual improvement in the general clinical condition as well as the laboratory parameters. Conclusions: This case report creates the awareness of possible presentation of pediatric LCH with isolated liver involvement. A high index of suspicion, carefully customized chemotherapeutic regimen may help in the timely diagnosis and successful management.